The last mapmaker - Soontornvat, Christina (Somerville, MA : Candlewick Press, 2022)
Joining an expedition to chart the southern seas, twelve-year-old mapmaker's assistant Sai, posing as a well-bred young lady with a glittering future, realizes she's not the only one on board harboring secrets when she discovers the ship's true destination.
Pub Weekly, February 2022
Kirkus Starred, February 2022
Booklist, February 2022
Horn Book, March 2022
5.6.
5-8.
Keywords: Cartography -- Juvenile fiction; Ocean travel -- Juvenile fiction; Social classes -- Juvenile fiction; Secrecy -- Juvenile fiction; Adventure stories; Cartography -- Fiction; Ocean travel -- Fiction; Social classes -- Fiction; Secrets -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Action and adventure fiction; Fantasy fiction